Water-based anti-flash-rust coating as well as preparation method and application thereof

By introducing acetone oxime into water-based anti-flash rust coatings and optimizing components and preparation methods, the problem that water-based coatings are prone to flash rust on the steel surface is solved, and excellent anti-flash rust effect and early water resistance are achieved, which meets the requirements of green and environmental protection.

CN119708937AActive Publication Date: 2025-03-28GUANGZHOU JOINTAS CHEM
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411963095.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

When using water-based coatings on the steel surface, due to the high volatility of water during the film formation process, electrochemical corrosion and flash rust, which affects the adhesion and corrosion resistance of the paint film. The existing anti-flash rust agents have problems such as high biotoxicity, environmental pollution, expensive price and poor anti-rust effect on iron substrates.

Method used

The aqueous anti-flash rust coating without toxic and harmful components is used to remove dissolved oxygen by introducing acetone oxime into component B, and by controlling the addition amount of components A and component B, combining high-selective pH adjusters, dispersants and film-forming additives, the composition and preparation method of the coating are optimized to achieve good anti-flash rust effect and early water resistance.

Benefits of technology

It achieves excellent anti-flash rust effect on metal substrates, has good early water resistance, short surface drying time, and does not affect the anti-corrosion performance of the paint film, which is in line with the concept of green environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217662240000061
    Figure BDA0005217662240000061
  • Figure BDA0005217662240000071
    Figure BDA0005217662240000071
  • Figure BDA0005217662240000072
    Figure BDA0005217662240000072
Patent Text Reader

Abstract

The invention discloses a water-based anti-flash-rust coating as well as a preparation method and application thereof, and belongs to the technical field of coatings. The water-based anti-flash-rust coating provided by the invention comprises a component A and a component B, the component A is prepared from the following components in parts by mass: 0 to 15 parts of water, 0.1 to 0.5 part of a pH (Potential of Hydrogen) regulator, 0.1 to 0.5 part of a dispersing agent, 0.01 to 0.1 part of a de-foaming agent, 1 to 10 parts of pigment, 30 to 60 parts of filler, 20 to 35 parts of resin, 0.6 to 4 parts of a coalescing agent, 0 to 0.2 part of a functional aid and 0.01 to 0.2 part of a thickening agent; the component B comprises the following component in parts by mass: 0.3-2 parts of acetoxime; the pH regulator comprises sodium hydroxide; the average molecular weight of the dispersing agent is 2000 to 4000; and the solid content of the component A is 69-71%. The water-based anti-flash-rust coating provided by the invention is excellent in early water resistance and anti-flash-rust property, and short in surface drying time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a water-based anti-flash rust coating and a preparation method and application thereof. Background Art

[0002] Water-based paint has the advantages of less environmental harm, convenient construction, good safety, easy storage and transportation, etc. It is increasingly widely used and is expected to completely replace solvent-based paint in the future. However, when water-based paint is used on steel surfaces, due to the high latent heat of volatilization of the dispersed medium water in the film-forming process and the slow evaporation rate, under the action of oxygen and water and ions in the water-based paint components, multiple small-area corrosion cells will form on the metal surface, electrochemical corrosion will occur, and flash rust will form, which will eventually lead to a significant decrease in the adhesion of the paint film, seriously affecting the anti-corrosion performance and aesthetics of the paint film.

[0003] In the prior art, it is usually necessary to add an anti-flash rust agent to the water-based coating on the surface of the metal substrate to avoid flash rust during the drying process of the coating. Early anti-flash rust agents mainly contain components such as chromates, dichromates, tetraborates, arsenates, nitrites, etc. For example, the main principle of sodium nitrite is to react with the metal surface to form a dense passivation film, thereby slowing down or preventing the corrosion of the substrate. These inorganic compounds generally have problems such as high biological toxicity, environmental pollution, and high prices, and their application is greatly limited. At present, most of the commercially available anti-flash rust agents are nitrites with large water solubility, but they only have an anti-rust effect on iron substrates. Not only are they used in large quantities and are easy to seep out, they will cause the paint film to have poor water resistance and seriously affect the anti-corrosion performance of the paint film, and nitrites are toxic and belong to indirect carcinogens, which do not conform to the concept of green environmental protection. Therefore, it is of great significance to develop an anti-flash rust agent with excellent anti-flash rust effect, green environmental protection, low price, and no effect on the performance of the paint film after application. Summary of the invention

[0004] The object of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a water-based anti-flash rust coating having excellent flash rust resistance and early water resistance and a shorter surface drying time, and a preparation method and application thereof.

[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a water-based anti-flash rust coating, the water-based anti-flash rust coating comprising a component A and a component B;

[0006] The component A comprises the following components in parts by mass: 0-15 parts of water, 0.1-0.5 parts of pH regulator, 0.1-0.5 parts of dispersant, 0.01-0.1 parts of defoamer, 1-10 parts of pigment, 30-60 parts of filler, 20-35 parts of resin, 0.6-4 parts of film-forming aid, 0-0.2 parts of functional aid, and 0.01-0.2 parts of thickener;

[0007] The B component includes the following components in parts by mass: 0.3-2 parts of acetone oxime;

[0008] The pH regulator includes sodium hydroxide and / or potassium hydroxide;

[0009] The average molecular weight of the dispersant is 2000-4000;

[0010] The solid content of the A component is 69-71%.

[0011] The water-based anti-flash rust coating provided by the present invention can effectively achieve a good anti-flash rust effect on a metal substrate without adding the existing conventional toxic, harmful or heavily polluting sodium nitrite and hexavalent chromium traditional anti-flash rust agents. The water-based anti-flash rust coating provided by the present invention has excellent early water resistance and a short surface drying time.

[0012] Specifically, in the first aspect, the present invention introduces acetone oxime into component B, which can effectively react with oxygen in water, thereby effectively removing the dissolved oxygen in the water-based anti-flash rust coating system itself and the dissolved oxygen that slowly infiltrates from the air during subsequent coating and coating drying; the equation for the reaction of acetone oxime with oxygen is 4(CH3)2C=N-OH+O2→4(CH3)2C=O+2N2+H2O, and the reaction of a small amount is 2(CH3)2C=N-OH+O2→2(CH3)2C=O+N2O+H2O. In the second aspect, the present invention controls the addition amount of component A and component B. Component A and component B within the appropriate range of parts can effectively consume the oxygen in the system itself and the dissolved oxygen that infiltrates subsequently while avoiding the influence of acetone oxime on the stability of the water-based anti-flash rust coating, thereby achieving a good anti-flash rust effect. In the third aspect, the present invention selects sodium hydroxide and / or potassium hydroxide as the pH regulator, which has strong alkalinity and is not volatile. During the drying process after the water-based anti-flash rust coating is applied, the pH value of the system will gradually increase, thereby helping the resin to quickly demulsify under high alkalinity conditions, thereby shortening the surface drying time. At the same time, due to the shortened surface drying time, the infiltration of dissolved oxygen can be further avoided, thereby improving the anti-flash rust effect of the product. In the fourth aspect, the present invention selects the average molecular weight of the dispersant to be 2000-4000. The dispersant in this molecular weight range can provide more anchoring groups, thereby having a better effect of reducing the viscosity of the system. Therefore, under the action of this type of dispersant, relatively more pigments and fillers can be added to increase the solid content of component A, thereby helping to achieve a faster surface drying speed of the product, and improving the anti-flash rust and early water resistance of the product. In the fifth aspect, the present invention further limits the solid content of component A to 69-71%. When the component A within this solid content range is mixed with the subsequent component B, the drying speed of the coating can be increased, thereby improving the anti-flash rust and early water resistance of the product; and it can also avoid the situation where the solid content is too high and cannot be prepared.

[0013] Illustratively, the average molecular weight of the dispersant may be any point value or any two point range value between 2000-4000, for example, 2000, 2200, 2400, 2600, 2800, 3000, 3200, 3400, 3600, 3800, 4000, etc.

[0014] In one embodiment, the dispersant is SN-5040 from Japan Sannopcord, and its average molecular weight is 3500.

[0015] The present invention has found that when SN-5040 is further selected as the dispersant, it can better anchor the group, reduce the viscosity of the system, and increase the solid content of the system, thereby helping to achieve good anti-flash rust effect and early water resistance of the product.

[0016] Exemplarily, the solid content of component A can be any point value or any two point range value between 69-71%, such as 69.0%, 69.2%, 69.4%, 69.6%, 69.8%, 70%, 70.2%, 70.4%, 70.6%, 70.8%, 71%, etc.

[0017] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the component A includes the following components in parts by mass: 10-12 parts of water, 0.2-0.3 parts of pH regulator, 0.2-0.3 parts of dispersant, 0.02-0.04 parts of defoamer, 1.2-2 parts of pigment, 45-55 parts of filler, 25-30 parts of resin, 1-2 parts of film-forming aid, 0-0.2 parts of functional additive, and 0.05-0.1 parts of thickener.

[0018] The present invention has found that the mass fractions of the components in component A and the subsequently added component B will interact with each other, thereby affecting the surface drying speed of the coating, and further affecting the anti-flash rust ability and early water resistance of the coating.

[0019] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the mass ratio of component A to component B is 1:(0.003-0.022).

[0020] Exemplarily, the mass ratio of component A to component B may be any point value or any two point range value between 1:(0.003-0.022), such as 1:0.003, 1:0.005, 1:0.008, 1:0.01, 1:0.012, 1:0.0014, 1:0.016, 1:0.018, 1:0.02, 1:0.022, etc.

[0021] The present invention has been found that components A and B in a suitable mass ratio range can well balance the anti-flash rust effect and the early water resistance effect. When the mass ratio of components A and B is further selected to be within the above range, the comprehensive effect of the obtained product is better.

[0022] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the resin includes anionic acrylic emulsion.

[0023] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the solid content of the resin is ≥47%.

[0024] In one embodiment, the resin is 0628 produced by Wanhua Chemical, and its solid content is 47%; or the resin is S984 produced by Foshan Badufu, and its solid content is 47%.

[0025] The present invention has found that selecting 0628 or S984 as the resin has a relatively fast drying speed and can cooperate well with other components to further improve the surface drying speed and early water resistance of the coating, thereby improving the anti-flash rust effect of the coating.

[0026] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the film-forming aid includes at least one of alcohol ester dodecanol and dipropylene glycol methyl ether.

[0027] The present invention has found that when the film-forming aid is further selected as at least one of alcohol ester dodecanol and dipropylene glycol methyl ether, both can have excellent synergistic effects with other components to help improve the drying speed of the coating, thereby achieving good anti-flash rust effect and early water resistance of the coating.

[0028] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the defoamer includes a silicone water-based defoamer.

[0029] In one embodiment, the defoaming agent is 901W from Germany's Digo; or the defoaming agent is 6791 from Shanghai Shenzhu Chemical.

[0030] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the pigment includes at least one of titanium dioxide, carbon black, iron black, phthalocyanine blue and phthalocyanine green.

[0031] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the filler includes at least one of calcium carbonate, talcum powder, natural barium sulfate, and precipitated barium sulfate.

[0032] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the thickener includes a polyurethane associative thickener.

[0033] In one embodiment, the thickener is Vesmody U-505 produced by Wanhua Chemical; or the thickener is RM-8W produced by Rohm and Haas; or the thickener is 5010S produced by Foshan Shierli New Materials Co., Ltd.

[0034] As a preferred embodiment of the water-based anti-flash rust coating of the present invention, the functional additive includes at least one of a wetting agent and a leveling agent.

[0035] The present invention has found that when defoamers, pigments, fillers, thickeners and functional additives are further selected as the above substances, the comprehensive performance of the obtained product is better.

[0036] In a second aspect of the present invention, the present invention provides a method for preparing a water-based anti-flash rust coating, the preparation method comprising the following steps:

[0037] (1) adding a pH regulator, a dispersant, a defoamer, a pigment and a filler to water in sequence while stirring and sand-grinding to obtain a slurry;

[0038] (2) adding resin, film-forming aid, thickener and functional aid to the slurry in sequence while stirring to obtain component A;

[0039] (3) Component A and component B are mixed evenly to obtain a water-based anti-flash rust coating.

[0040] In the preparation method of the anti-flash rust coating provided by the present invention, by selecting a specific adding sequence, good comprehensive performance of the coating can be better achieved.

[0041] As a preferred embodiment of the preparation method of the present invention, in the step (1), the fineness of the slurry is less than 50 μm.

[0042] As a preferred embodiment of the preparation method of the present invention, the viscosity of component A is ≤120KU.

[0043] The present invention has found that the fineness range of the appropriate slurry and the viscosity range of component A can better achieve the early water resistance and anti-flash rust properties of the coating.

[0044] In the third aspect of the present invention, the present invention provides the use of the water-based anti-flash rust coating in preparing a surface protective layer of a metal substrate.

[0045] The water-based anti-flash rust coating provided by the present invention has excellent anti-flash rust property and early water resistance, and can be effectively applied to the protection of the surface of a metal substrate to achieve good effects.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The water-based anti-flash rust coating provided by the present invention can effectively achieve a good anti-flash rust effect on a metal substrate without adding the existing conventional toxic, harmful or heavily polluting sodium nitrite and hexavalent chromium traditional anti-flash rust agents, and the water-based anti-flash rust coating provided by the present invention has excellent early water resistance and a short surface drying time; specifically, the obtained water-based anti-flash rust coating is normal in the flash rust test, the early water resistance is also normal, and the surface drying time is less than 30 minutes. At the same time, the raw materials of the water-based anti-flash rust coating provided by the present invention are easy to obtain, the preparation method is simple to operate, and is conducive to actual production. DETAILED DESCRIPTION

[0048] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0049] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0050] Dispersant 1: average molecular weight 3500, SN-5040, San Nopco, Japan;

[0051] Dispersant 2: average molecular weight 1350, HP2000, Anshan Huihong New Materials Co., Ltd.;

[0052] Dispersant 3: average molecular weight 10000, B190, Foshan Shierli New Materials Co., Ltd.;

[0053] Defoamer: 901W, Digo, Germany;

[0054] Pigment: titanium dioxide, commercially available;

[0055] Filler: calcium carbonate, commercially available;

[0056] Resin 1: anionic acrylic emulsion, solid content 47%, 0628, Wanhua Chemical;

[0057] Resin 2: anionic acrylic emulsion, solid content 47%, S984, Foshan Ba ​​De Fu;

[0058] Film-forming aid: alcohol ester twelve, commercially available;

[0059] Thickener: Vesmody U-505, Wanhua Chemical;

[0060] Acetone oxime: Tianjin Damao Chemical Reagent Factory.

[0061] Examples 1-9 and Comparative Examples 1-8

[0062] The present invention provides a water-based anti-flash rust coating according to the embodiment and comparative example. The components (parts by mass) of the water-based anti-flash rust coating are shown in Table 1-2.

[0063] The solid content of component A is tested in accordance with GB / T 1725-2007 Determination of non-volatile matter content of paints, varnishes and plastics; the viscosity of component A is tested in accordance with GBT 1723-1993.

[0064] Table 1

[0065]

[0066]

[0067] Table 2

[0068]

[0069]

[0070] The preparation method of the water-based anti-flash rust coating provided in Example 1 comprises the following steps:

[0071] (1) adding a pH regulator, a dispersant, a defoamer, a pigment and a filler to water in sequence while stirring and sand-grinding to obtain a slurry, wherein the fineness of the slurry is less than 50 μm;

[0072] (2) adding resin, film-forming aid, thickener and functional aid to the slurry in sequence while stirring to obtain component A;

[0073] (3) Component A and component B are mixed evenly to obtain a water-based anti-flash rust coating.

[0074] The preparation methods of Examples 2-9 and Comparative Examples 1-8 are consistent with that of Example 1.

[0075] Example 10

[0076] The embodiment of the present invention provides a water-based anti-flash rust coating, the only difference between the water-based anti-flash rust coating and the embodiment 1 is that 0.05 parts of a wetting agent (BYK-302) is added.

[0077] Comparative Example 9

[0078] The comparative example of the present invention provides a water-based anti-flash rust coating, which is different from Example 1 only in the difference in the preparation method. The preparation method of this comparative example is:

[0079] (1) adding a dispersant, a defoamer, a pigment and a filler to water in sequence while stirring and sand-grinding to obtain a slurry, wherein the fineness of the slurry is less than 50 μm;

[0080] (2) adding a pH adjuster, a resin, a film-forming aid, a thickener and a functional aid to the slurry in sequence while stirring to obtain component A;

[0081] (3) Component A and component B are mixed evenly to obtain a water-based anti-flash rust coating.

[0082] Effect example

[0083] The effect examples of the present invention verify the performance of the water-based anti-flash rust coatings prepared in Examples 1-10 and Comparative Examples 1-9, specifically including the following aspects:

[0084] 1. Surface drying time: refer to the provisions of GB / T 1728-2020, where surface drying is carried out according to the provisions of surface drying time method B;

[0085] 2. Anti-flash rust property: Place the test panel in an environment with a temperature of 25°C and a humidity of 95% RH or above and visually observe whether there is rust on the surface of the coating. If rust is found on the surface, record the time when the rust is found. If no rust is found after 24 hours of visual observation, immediately soak the test panel in methyl ethyl ketone solvent, remove the coating (use wooden tools if necessary), and visually observe whether there are rust spots on the substrate. If there are no rust spots on the substrate, it is rated as "normal".

[0086] The test plate preparation method is as follows: the water-based anti-flash rust paint is diluted with appropriate water to a test spray viscosity of 65±2KU, and air spraying is adopted, and the dry film thickness is controlled to be 80μm;

[0087] 3. Early water resistance: immerse half of the coating of the prepared and cured test panels in distilled water and observe. If at least one of the three test panels has coating defects such as blistering, rust, cracking or peeling, record the corresponding immersion time. If no coating defects such as blistering, rust, cracking or peeling are observed after 5 hours of immersion, take out the test panels and observe visually under natural sunlight or artificial sunlight as specified in GB / T 37356-2019. Further confirm that at least two of the three test panels have no coating defects such as blistering, rust, cracking and peeling, and no obvious discoloration is observed in the immersion area compared with the non-immersion area after the test panels are restored under standard conditions for 2 hours, and then it is evaluated as "no abnormality";

[0088] The test plate curing method is as follows: the prepared test plate is placed in an environment with a temperature of 25°C and a humidity of 50% RH for a curing time of 24 hours;

[0089] The test results are shown in Table 3;

[0090] Table 3

[0091]

[0092] It can be seen from Table 3 that when the technical solution provided by the present invention is adopted, the obtained product has good flash rust resistance and early water resistance, and the surface drying time of the obtained product is short; specifically, the surface drying time of the obtained product is less than 30 minutes, and both the flash rust resistance and early water resistance tests can be passed normally;

[0093] It can be seen from Example 1 and Comparative Examples 1-2 that the mass fraction of acetone oxime has a significant effect on the performance of the product. When the mass fraction of acetone oxime in Comparative Example 1 is too small, the obtained product fails the flash rust resistance test, and rust is observed after being placed for 15 minutes, that is, the flash rust resistance is poor; when the mass fraction of acetone oxime in Comparative Example 2 is too large, the surface drying time of the obtained product is too long, reaching 40 minutes, and fails the early water resistance test, and blistering occurs after immersion for 4 hours, that is, the early water resistance is poor;

[0094] It can be seen from Example 1 and Comparative Examples 3-4 that the solid content of component A will also affect the comprehensive performance of the product. When the solid content of component A in Comparative Example 3 is too low, the surface drying time of the obtained product is too long, reaching 42 minutes, and the obtained product fails the flash rust resistance test, and rust appears 4 hours after being placed, that is, the flash rust resistance is poor; when the solid content of component A in Comparative Example 4 is too high, the corresponding product cannot be prepared;

[0095] It can be seen from Example 1 and Comparative Example 5 that when other conventional pH adjusters such as ammonia water are used, the obtained product fails the flash rust resistance test, and rust is observed after being placed for 10 minutes, that is, the flash rust resistance is poor;

[0096] It can be seen from Example 1 and Comparative Example 6 that when other conventional flash rust preventers such as sodium nitrite are used, the obtained product passes the flash rust prevention test normally, but fails the early water resistance test, and blistering occurs after immersion for 2 hours, that is, the early water resistance is poor;

[0097] It can be seen from Example 1 and Comparative Examples 7-8 that the selection of dispersants will also affect the comprehensive performance of the product. When the average molecular weight of the dispersant in Comparative Example 7 is too low, the obtained product fails the early water resistance test and foaming occurs after immersion for 3 hours, that is, the early water resistance is poor; when the average molecular weight of the dispersant in Comparative Example 8 is too high, the corresponding product cannot be prepared;

[0098] It can be seen from Example 1 and Comparative Example 9 that the order of adding the pH adjuster in the preparation method will also affect the performance of the product. When the pH adjuster is added after the slurry is formed, the corresponding product cannot be prepared.

[0099] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A water-based anti-flash rust coating, characterized in that: The water-based anti-flash rust coating comprises component A and component B; The component A comprises the following components in parts by mass: 0-15 parts of water, 0.1-0.5 parts of pH regulator, 0.1-0.5 parts of dispersant, 0.01-0.1 parts of defoamer, 1-10 parts of pigment, 30-60 parts of filler, 20-35 parts of resin, 0.6-4 parts of film-forming aid, 0-0.2 parts of functional aid, and 0.01-0.2 parts of thickener; The B component includes the following components in parts by mass: 0.3-2 parts of acetone oxime; The pH regulator includes sodium hydroxide and / or potassium hydroxide; The average molecular weight of the dispersant is 2000-4000; The solid content of the A component is 69-71%.

2. The water-based anti-flash rust coating according to claim 1, characterized in that: The component A comprises the following components in parts by mass: 10-12 parts of water, 0.2-0.3 parts of pH regulator, 0.2-0.3 parts of dispersant, 0.02-0.04 parts of defoamer, 1.2-2 parts of pigment, 45-55 parts of filler, 25-30 parts of resin, 1-2 parts of film-forming aid, 0-0.2 parts of functional aid, and 0.05-0.1 parts of thickener.

3. The water-based anti-flash rust coating according to claim 1, characterized in that: The mass ratio of the component A to the component B is 1:(0.003-0.022).

4. The water-based anti-flash rust coating according to claim 1, characterized in that: The resin includes anionic acrylic emulsion.

5. The water-based anti-flash rust coating according to claim 3, characterized in that: The solid content of the resin is ≥47%.

6. The water-based anti-flash rust coating according to claim 1, characterized in that: The film-forming aid includes at least one of alcohol ester dodecaned and dipropylene glycol methyl ether; and / or, the defoamer comprises an organic silicon aqueous defoamer; And / or, the pigment includes at least one of titanium dioxide, carbon black, iron black, phthalocyanine blue and phthalocyanine green; And / or, the filler includes at least one of calcium carbonate, talcum powder, natural barium sulfate, and precipitated barium sulfate; and / or, the thickener comprises a polyurethane associative thickener; And / or, the functional additive includes at least one of a wetting agent and a leveling agent.

7. The method for preparing the water-based anti-flash rust coating according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) adding a pH regulator, a dispersant, a defoamer, a pigment and a filler to water in sequence while stirring and sand-grinding to obtain a slurry; (2) adding resin, film-forming aid, thickener and functional aid to the slurry in sequence while stirring to obtain component A; (3) Component A and component B are mixed evenly to obtain a water-based anti-flash rust coating.

8. The preparation method according to claim 7, characterized in that: In the step (1), the fineness of the slurry is less than 50 μm.

9. The preparation method according to claim 7, characterized in that: The viscosity of the A component is ≤120KU.

10. Use of the water-based anti-flash rust coating according to any one of claims 1 to 6 in preparing a surface protective layer of a metal substrate.

Citation Information

Patent Citations

  • Water-based acrylic acid anticorrosive primer for steel structure and preparation method of water-based acrylic acid anticorrosive primer

    CN115651467A

  • Isolation coating for hot-melt pressure-sensitive adhesive and preparation method of isolation coating

    CN117757315A

  • Environment-friendly ferro-aluminum antirust agent in high-temperature tap water medium as well as preparation method and application of ferro-aluminum antirust agent

    CN118621321A